The culture of prison violence - Byrne, James M.; Hummer, Donald C.; Taxman, Faye S. (Pearson/Allyn & Bacon, 2008)
The nature and extent of prison violence / James M. Byrne, Don Hummer -- Does what happens in prison stay in prison? : examining the reciprocal relationship between community and prison culture / Jacob I. Stowell, James M. Byrne -- Examining the impact of institutional culture (and culture change) on prison violence and disorder : an evidence-based review / James Byrne, Don Hummer, Faye Taxman -- Legitimacy and imprisonment revisited : some notes on the problem of order ten years after / Richard Sparks -- Why prison culture matters / Alison Liebling -- Performance, domesticity, and disorder : the communicative quality of prison violence / Elaine Crawley, Peter Crawley -- The impact of prison culture on the treatment and control of mentally ill offenders / Arthur J. Lurigio, Jessica Snowden -- A culture of violence in England's prison system : an assessment of causes and solutions / Kimmitt Edgar, Prison Reform Trust -- Prison violence, prison culture, and offender change : new directions for theory, research, and policy / James M. Byrne